Silicon improves the photosynthetic performance of oat leaves infected with Puccinia graminis f. sp. avenae - Li, Yinghao; Liu, Jinghui; Lv, Pin; Mi, Junzhen; Zhao, Baoping (Frontiers in Plant Science, 2022)
Stem rust, caused by Puccinia graminis f. sp. avenae (Pga) is a key disease affecting oat production worldwide. Silicon (Si) plays an essential role in enhancing plant resistance against pathogens. However, the scientific evidence of Si-mediated stem rust resistance of oat from the photosynthetic perspective has not been reported. The specific objective of this research was to investigate the effects of Si application on disease inhibition, photosynthetic gas exchange parameters, light response parameters, photosynthetic pigments and chlorophyll fluorescence parameters under Pga infection. Our results illustrated that Si application significantly reduced rust severity while the other parameters like net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci) and transpiration rate (Tr) were significantly increased. Si application increased maximum photosynthetic rate (Pnmax) and light saturation point (LSP), while reduced the dark respiration rate (Rd) and light compensation point (LCP). The results also indicated that Si application significantly increased the activities of maximum fluorescence (Fm), variable fluorescence (Fv), maximum quantum yield of photosystem II (Fv/Fm), photochemical quenching (qP), photosynthetic performance index (PIABS), actual PSII quantum yield (ΦPSII), electron transfer rate (ETR), the absorbed light energy per unit reaction center (ABS/RC) and the dissipated energy per unit reaction center (DIo/RC), whereas it decreased the minimal fluorescence (Fo), non-photochemical quenching (NPQ), the absorbed light energy used for electron transfer per unit reaction center (ETo/RC) and the absorbed light energy used for reduction of QA per unit reaction center (TRo/RC). The contents of chlorophyll a, b and carotenoids were also increased due to the change in the activity of parameters due to Si application as mentioned above. In conclusion, the results of the current study suggests that Si imparts tolerance to the stem rust possibly by the underlying mechanisms of improving gas exchange performance, and efficiency of the photochemical compounds in oat leaves.